Islands versus rocks: claims over maritime entitlements and interpretation of Article 121 of the UNCLOS - Hamid, Abdul Ghafur@Khin Maung Sein (2018)
Maritime Territorial disputes, including the South China Sea, are very sensitive in nature and may even lead to coercive means. The main emphasis of the present paper is against man-made constructions which would ultimately change a small uninhabited rock or coral atoll to be a full-fledged island, entitled to EEZ and CS. This is also the major concern of States, including Malaysia. The relevant States should exercise restraints in the construction of additional installations, especially military, on the disputed features so as not to hamper peace and stability in the SCS. Consultations under Declaration on Conduct of Parties in the SCS (DOC) 2002 between China and ASEAN are not adequate and it has to be strengthened with Code of Conduct in the SCS (COC). Since China is against any third party settlement, negotiations are the only alternative and serious and meaningful negotiations should be conducted between interested parties.